Routledge handbook of south-south relations - Fiddian-Qasmiyeh, Elena 1978-; Daley, Patricia (Routledge, Taylor & Francis Group, 2020)
South-South cooperation is becoming ever more important to states, policy-makers and academics. Many Northern states, international agencies and NGOs are promoting South-South partnerships as a means of ‘sharing the burden’ in funding and undertaking development, assistance and protection activities, often in response to increased political and financial pressures on their own aid budgets.
Keywords: bicssc / Human geography; bicssc / Regional geography; bicssc / Society & culture - general; bicssc / Anthropology; bisacsh / POLITICAL SCIENCE / Globalization; bisacsh / SOCIAL SCIENCE / Developing & Emerging Countries; Süd-Süd-Beziehungen; Aufsatzsammlung